A SEMIOTIC ANALYSIS OF THE STATUE SCENE IN ANDREI TARKOVSKY’S NOSTALGHIA USING ROLAND BARTHES FIVE NARRATIVE CODES - ROLAND SPAHIU (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Andrei Tarkovsky is one of the most prominent directors in the world of movies. People recognize him for his poetic visual style and images that are out of this world. His Italian movie Nostalghia (1983) was a big step forward in his career.It was about exile, remembrance, and spirituality. The statue sequence is one of the most perplexing portions of the movie.It's when visual imagery, cultural symbolism, and metaphysical tension all come together. This study analyzed the situation through the lens of Roland Barthes's concept of the five narrative codes.The study utilized a qualitative research design and a close reading methodology to analyze visual composition, aural design, dialogue, and symbolic layering. We delineated and elucidated each of Barthes's narrative codes. The hermeneutic code revealed enigmas and narrative delays; the proairetic code illustrated gestures and movements that engendered anticipation; the semic code demonstrated how lighting, gestures, and auditory motifs could convey varied meanings; the symbolic code elucidated the interpretation of binary oppositions such as life/death and homeland/exile; and the cultural code contextualized the scene within broader intertextual frameworks, including Russian memory, and Italian artistic heritage. The findings confirmed that Barthes's framework effectively clarified the scene's complex structure while simultaneously revealing its limitations.It was hard to put some feelings into words, like quietness, stillness, and the materiality of stone. This is in line with Barthes's concept of opaque meaning and Tarkovsky's metaphysical aesthetics. The study found that the statue scene served as both a coded text and an emotive, spiritual tableau. These findings improve semiotic methods in Tarkovsky studies and show how important it is to combine structural and emotional interpretations when analyzing movies.